Incorporating Object-Oriented Metrics Into A Reverse Engineering Tool - Eshah, Nida Bashir (2003)
This work explains the use of object-oriented software product metrics with their thresholds and how they could be incorporated into a reverse engineering tool that visualizes the architectural components of a software system. Visualizing. Object-Oriented C++ ( VOO++), reverse engineering tool that visualizes C++ objectoriented source code, is enhanced and reproduced to become a Visualizing and Measuring C++ ( VMCPP) tool that visualizes and measures object-oriented C++ files. VMCPP assists the software developer in extracting and interpreting the components of a software system. Unified Modeling Language (UML) class diagrams are produced to graphically represent the classes involved in implementing a software system. Thresholds are used within VMCPP to separate the extracted metrics values into normal values and critical values.